The effect of auditory stimulus training on swimming start reaction time. Issue 4 (4th July 2019) - Papic, Christopher; Sinclair, Peter; Fornusek, Che; Sanders, Ross
Abstract: Task-specific auditory training can improve sensorimotor processing times of the auditory reaction time (RT). The majority of competitive swimmers do not conduct habitual start training with the electronic horn used to commence a race. We examined the effect of four week dive training interventions on RT and block time (BT) of 10 male adolescent swimmers (age 14.0 ± 1.4 years): dive training with auditory components (speaker and electronic horn) ( n  = 5) and dive training without auditory components ( n  = 5). Auditory stimulus dive training significantly reduced swimming start RT, compared with dive training without auditory components ( p  < 0.01), with a group mean RT reduction of 13 ± 9 ms. Four of the five swimmers that received auditory stimulus training showed medium to large effect size reductions in RT ( d  = 0.74; 1.32; 1.40; 1.81). No significant changes to swimmers' BTs were evident in either dive training intervention. The adolescent swimmers' results were compared against six male elite swimmers (age 19.8 ± 1.0 years). The elite swimmers had significantly shorter BTs ( p  < 0.05) but no significant difference in RTs. Auditory stimulus dive training should be explored further as a mechanism for improving swimming start performance in elite swimmers who have pre-established optimal BTs.